Long-term quality of life and posttraumatic stress following elective cardiac surgery: preliminary findings of a 5-year follow-up study - Gražulytė, Daiva; Kazlauskas, Evaldas; Norkienė, Ieva; Kolevinskaitė, Smiltė; Kezytė, Greta; Urbanavičiūtė, Indrė; Sabestinaitė, Akvilė; Korsakaitė, Gintarė; Želvienė, Paulina; Ringaitienė, Donata; Šostakaitė, Gintarė; Šipylaitė, Jūratė (Acta medica Lituanica, 2019)
Background. Heart surgery is a major stressful event that can have a significant negative effect on patients’ quality of life (QoL) and may cause long-term posttraumatic stress reactions. The aim of this pilot study was to estimate the longitudinal change and predictors of health-related quality of life (HRQOL) dynamics and identify factors associated with PTS at 5-year follow-up (T2) after elective cardiac surgery and associations with pre-surgery (T1) QoL. Materials and methods. Single-centre prospective study was conducted after Regional Bioethics Committee approval. Adult consecutive patients undergoing elective cardiac surgery were included. HRQOL was measured using the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) questionnaire before (T1) and 5-years after (T2) cardiac surgery. Posttraumatic stress was assessed using the International Trauma Questionnaire. Results. The pilot study revealed a significant positive change at 5-year follow-up in several domains of SF-36: physical functioning (PF), energy/fatigue (E/F), and social functioning (SF). Prolonged postoperative hospital stay was associated with change in SF (p < 0.01), E/F (p < 0.05) and emotional well-being (p < 0.05). The percentage of patients that had the posttraumatic stress disor. der (PTSD) at T2 was 12.2%. Posttraumatic stress symptoms were associated with longer hospitalization after surgery (p < 0.01). Conclusions. HRQOL improved from baseline to five years postoperatively. Patients with lower preoperative HRQOL scores tended to have a more significant improvement of HRQOL five years after surgery. A prolonged postoperative hospital stay had a negative impact on postoperative social functioning, energy/fatigue, and emotional well-being. Increased levels of PTSD were found in cardiac surgery patients following five years after the surgery.
Keywords: cardiac surgery; health-related quality of life; posttraumatic stress